Radiotherapy combined with anlotinib for refractory leiomyosarcoma: a case report and literature review - Li, Ziming; Yu, Xiuchun; Xu, Ming (Frontiers in Oncology, 2025)
Refractory leiomyosarcoma (LMS) is characterized by notoriously high recurrence rates and poses significant surgical challenges due to its anatomical complexity and invasive growth patterns. When complete surgical resection proves unattainable, radiotherapy has emerged as a cornerstone therapeutic modality, with emerging evidence suggesting synergistic effects when combined with novel chemotherapeutic agents. This study presents an illustrative case of advanced popliteal fossa LMS managed through precision radiotherapy combined with anlotinib, a multi-target tyrosine kinase inhibitor, which achieved sustained local tumor control and progression-free survival over 18 months of follow-up. Notably, the comprehensive management strategy for treatment-related complications, particularly radiation-induced dermatitis and hematological toxicity, demonstrated clinically validated mitigation approaches through phased dose adjustment and supportive care protocols. The therapeutic paradigm described herein provides valuable insights for optimizing multimodal management of refractory soft tissue sarcomas, highlighting the potential of targeted therapy-radiotherapy combinations while emphasizing the critical importance of proactive complication surveillance in contemporary oncological practice.